2017
DOI: 10.1108/bfj-10-2016-0448
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity of Brazilian cooking skills and healthy eating questionnaire by the known-groups method

Abstract: Purpose The purpose of this paper is to describe the results of the construct validity by the known-groups method of a Brazilian cooking skills and healthy-eating questionnaire. Design/methodology/approach Responses obtained from university students (n=767) for Brazilian-Portuguese cooking skills and health eating questionnaire, surveyed online, were submitted to construct validity comparing two known groups. The t-test was used to compare differences between gender (male and female) and the level of cooking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 42 publications
0
53
0
Order By: Relevance
“…The development of new instruments of evaluation, because it is not an easy task, is only encouraged in the absence of another instrument adequate to the practices and the reality under study [13,18,19,23], a situation which was observed in this study [3,4,[11][12][13][14][15]. As an advantage, the CSI is short, easy to apply and standardized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The development of new instruments of evaluation, because it is not an easy task, is only encouraged in the absence of another instrument adequate to the practices and the reality under study [13,18,19,23], a situation which was observed in this study [3,4,[11][12][13][14][15]. As an advantage, the CSI is short, easy to apply and standardized.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of cooking skills adopted in this research was that of DGBP [6]. The literature review verified a lack of an instrument adapted to the Brazilian reality contemplating such a definition [3,4,[11][12][13][14][15]].…”
Section: Development Of the Csimentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire items were distributed within eight measures about cooking skills and healthy eating, and a group of items about personal, cooking and demographic characteristics. The process of cross-culturally adaptation and validation of the instrument to Brazil is ongoing and the first paper was published in a scientific journal [ 67 ].…”
Section: Methodsmentioning
confidence: 99%